Passivação de aços contendo baixo cromo (4 - 6 %massa) como reforços de matrizes cimentícias curadas por carbonatação - Felipe, Rafaela Farinha (2023)
Reinforced concrete, composed of Portland cement and carbon steel, is an affordable material for projects, with satisfactory mechanical properties for civil construction. The alkaline solution in the concrete's pores guarantees the steel's ability to spontaneously passivate. However, cement production manufacturing involves high CO2 emissions. Therefore, alternatives for replacing Portland cement with cements with a low CO2 footprint have been developed. This work combined the use of steels with low percentages of chromium (4% and 6% by mass) in synthetic concrete solution cured by carbonation. The steels were produced in an arc furnace, rolled and annealed, with the aim of mimicking the grain size. The characterization of the steels was carried out using x-ray diffraction (XRD), optical microscopy and spark optical emission spectrometry. The steels subjected to synthetic solution were evaluated by electrochemical methods of open circuit potential (OCP), linear polarization resistance (LPR), electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PP). The passive film was evaluated using XPS (X-ray Photoelectron Spectroscopy). The steels produced had a ferritic structure. Electrochemical tests showed that conventional rebars are susceptible to corrosion in the matrix cured by carbonation. Steels containing chromium contents of 4% and 6% showed passivation, as confirmed by OCP values > -150 mVHg/HgO, Rp (resistance to polarization) > 300 kΩ.cm², high impedance modulus at 10 mHz (׀ Z10 ׀mHz > 106 Ω) and formation of a passivation plateau along the anodic potentiodynamic polarization. The XPS tests also showed the presence of compounds such as Cr2O3 and CrOOH, typical constituents of resistant passive films. Therefore, this study showed the possibility of producing low chromium steels that are passivated in cementitious matrices solution cured by carbonation.